Received strength signal intensity performance analysis in wireless sensor network using Arduino platform and XBee wireless modules - Alejandro Cama-Pinto; Gabriel Piñeres-Espitia; José Caicedo-Ortiz; Elkin Ramírez-Cerpa; Leonardo Betancur-Agudelo; Francisco Gómez-Mula (International Journal of Distributed Sensor Networks, 2017)
Today, through the monitoring of agronomic variables, the wireless sensor networks are playing an increasingly important role in precision agriculture. Among the emerging technologies used to develop prototypes related to wireless sensor network, we find the Arduino platform and XBee radio modules from the DIGI Company. In this article, based on field tests, we conducted a comparative analysis of received strength signal intensity levels, calculation of path loss with “log-normal shadowing” and free-space path loss models. In addition, we measure packet loss for different transmission, distances and environments with respect to an “Arduino Mega” board, and radio modules XBee PRO S1 and XBee Pro S2. The tests for the packet loss and received strength signal intensity level show the best performance for the XBee Pro S2 in the indoor, outdoor, and rural scenarios.